(untitled) (The Review of Diabetic Studies, 2024)
This study explored the interrelationship between trust, professional role identity, and patient-centered coordination within the framework of removable orthodontic care, emphasizing the significance of interprofessional collaboration in achieving effective and ethical patient outcomes. Through a phenomenological synthesis, the research revealed that trust acts as the foundational element in all collaborative healthcare interactions, shaping communication, cooperation, and collective accountability. The results demonstrated that when trust is established through competence, transparency, and mutual respect, it facilitates stronger team cohesion and patient satisfaction. Similarly, role identity was shown to be pivotal in determining how professionals perceive and enact their responsibilities within multidisciplinary settings. A clearly defined role identity enhances mutual recognition, reduces conflict, and strengthens the sense of interdependence among team members. Furthermore, the study underscored that patient-centered coordination serves as the operational bridge linking interpersonal trust with systemic collaboration, translating professional synergy into tangible improvements in care quality and efficiency. The integration of the Theory of Planned Behavior, Role Identity Theory, and the Relational Coordination Model provided a multidimensional understanding of these constructs, highlighting both behavioral and relational determinants of teamwork. The theoretical findings suggest that fostering interprofessional education, ethical leadership, and organizational support mechanisms can enhance collaborative performance and professional satisfaction. Ultimately, the research concludes that effective orthodontic care depends on cultivating a trust-based, ethically grounded, and identity-conscious model of collaboration one that aligns professional autonomy with shared patient goals and upholds the moral and social values essential to healthcare excellence.